Risk factors of Helicobacter pylori infection in children: a cross-sectional study in Chenani - Gupta, Vinod; Gupta, Akhil; Gupta, Sucheta (International Journal of Advances in Medicine, 2021)
Background: H. pylori infections generally occur early in childhood and continue to cause gastric diseases later in life. Epidemiological studies suggest its transmission through fecal to oral and oral to oral routes. Several factors control this transmission including socioeconomic status, quality of drinking water, personal and environmental hygiene, contamination of food, overcrowding and density of population. Methods: A cross-sectional study, involving 100 children aged 1 to 15 years, presenting gastrointestinal complaints was conducted in the department of medicine, district hospital, Udhampur, Jammu, Jammu and Kashmir, India from October 2019 to March 2020. Children with the pathology of central nervous system or with any other known pathology were excluded. Results: Majority of children belonged to the group >6, ≤11 years age (41%), 89% of children were school-going and 78% of participants belonged to the rural areas. Major economic activity of the participants came out to be business and trading (31%), as much as 62% of households were having a size of >4 persons per unit. As many as 24 children were found positive for antigen test upon stool sample examination. The infection rate was significantly higher among children having unsafe source of drinking water (14/24, 58.3%) and poor sanitation facilities (18/24, 66.7%). Overcrowding at home due to bigger household size was found to be a major risk factor among children. Conclusions: The prevalence of H. pylori among children was quite high. Major risk factors included sanitation and drinking water facilities at home and at schools.